Does Market Orientation Affect the Performance of SMEs? - Francis Osei; Ernest Yiadom Boakye; Owusu Ansah Kwadwo; Alfred Atakora; Beverley Wilson-Wünsch (Research Synergy Foundation, 2025)
This paper investigates the impact of market orientation on the performance of small and medium-sized enterprises (SMEs) in Kumasi, Ghana, emphasizing its relevance for emerging economies. The study addresses a gap in empirical research on this topic, underscoring its significance. Data was collected through a structured questionnaire, resulting in 200 valid responses from top executives and managers, which were subsequently analyzed using Structural Equation Modeling (SEM) to explore the relationships between market orientation and firm performance. The findings reveal a significant negative relationship between competitor orientation and firm performance, while customer orientation and inter-functional orientation show positive and significant correlations with firm performance. These results underscore the critical role of customer and market-oriented dimensions in enhancing SME performance, advocating for a stronger market orientation within SMEs. Additionally, the study suggests that new companies should focus on developing a market-oriented profile and strategically utilizing their resources. It emphasizes the importance of caution for companies seeking to adopt market orientation, considering industry context, timing, and strategies for leveraging internal resources and core competencies to achieve optimal performance.